PENGEMBANGAN LKPD MATERI PERUBAHAN LINGKUNGAN BERBASIS RUBRIK KEMAMPUAN KOLABORASI 21st CENTURY LEARNING DESIGN KELAS X KURIKULUM MERDEKA - Sa'adah, Mega Shofia; Prafitasari, Aulya Nanda; Eurika, Novy (Program Studi Pendidikan IPA FKIP Universitas Jember, 2024)
21st century learning focuses on student-centered learning, no longer teacher-centered. In 21st century learning, it encourages students to have collaboration skills. In the classroom learning process, collaboration abilities can be measured by working on LKPD (students worksheet) based on collaboration abilities. This research aims to develop LKPD learning media based on collaboration ability rubrics, to determine the level of validity, practicality and effectiveness of LKPD material on environmental change based on collaboration ability rubrics. This research was carried out at SMA Muhammadiyah 3 Jember. This type of research is development research, with a 4D development model. Data collection used teacher and student needs assessment questionnaires, validation tests and continued with student response assessments and pretest posttest trials. Based on data analysis, the results obtained were that the average validity test by three validators was 91.30% in the